Enhancing Critical Thinking and Spiritual Attitudes through Qur’an-Integrated Solar System Learning in Pesantren-Based Madrasah Aliyah: A Quasi-Experimental Study - Nikmatul Khoiriyah; Ani Rusilowati; Sulhadi (Universitas Nurul Huda, 2026)
This study aims to examine the effectiveness of Qur’an-integrated solar system teaching materials in improving students’ spiritual attitudes and critical thinking skills. A quasi-experimental method with a pretest–posttest control group design was employed. The participants consisted of 105 students from two pesantren-based Madrasah Aliyah in Semarang and Kendal, divided into an experimental group (n = 51) and a control group (n = 54). The experimental group was taught using Qur’an-integrated teaching materials, while the control group used conventional materials. Data were collected through a validated spiritual attitude questionnaire and an essay-based critical thinking test. Data were analyzed using normalized gain and independent sample t-test. The results showed that the experimental group achieved a higher improvement in spiritual attitudes (g = 0.52, moderate) compared to the control group (g = 0.14, low). Similarly, critical thinking skills in the experimental group (g = 0.55, moderate) were significantly higher than in the control group (g = 0.16, low). Independent sample t-tests revealed significant differences between groups in critical thinking skills (t = -2.88, p = 0.006) and spiritual attitudes (t = 3.41, p = 0.001). These findings indicate that Qur’an-integrated teaching materials are effective in enhancing both affective and cognitive domains. This study contributes to the development of integrative physics learning that bridges scientific concepts and spiritual values in Islamic-based education.